MORPHOLOGICAL AND FUNCTIONAL CHANGES OF THE HEPATIC VASCULAR BED UNDER THE CONDITIONS OF MODELING ALCOHOLIC HEPATITIS - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Neporada, K.S. (World of Medicine and Biology, 2021)
The experiments were performed on 30 white adult outbred male rats weighing 180–220 g. Animals were divided into 2 groups: I – control (n=6); II – animals with simulated alcoholic hepatitis (n=24). We studied the total NO synthase activity, peroxynitrite, nitrites and nitrosothiols concentrations in rat liver homogenate. We also studied morphometric parameters of hemomicrocirculatory tract of the rat liver. On the 7th day of modeling of alcoholic hepatitis interparticle arteries and veins and lobular arterioles narrow. The central vein dilates. The sinusoidal capillaries around the hepatic triad and central vein dilate. Alcoholic hepatitis increases the total activity of NO synthases, the concentration of peroxynitrites and nitrosothiols, but reduces the concentration of nitrites in the liver of rats on day 7 of the experiment. Nitric oxide and its metabolites play an important role in the regulation of the resistant part of the hemomicrocirculatory tract of the rat liver in the first three days of the experiment. Further redistribution of nitric oxide cycle metabolites leads to an increase in the concentration of peroxynitrite, which is a factor of secondary alteration.
Keywords: liver; alcoholic hepatitis; rats